Multidimensional poverty and inequality - Rolf Aaberge; Andrea Brandolini (Statistics Norway, Research Department, 2014)
This paper examines different approaches to the measurement of multidimensional inequality and poverty. First, it outlines three aspects preliminary to any multidimensional study: the selection of the relevant dimensions; the indicators used to measure them; and the procedures for their weighting. It then considers the counting approach and the axiomatic treatment in poverty measurement. Finally, it reviews the axiomatic approach to inequality analysis. The paper provides a selective review of a rapidly growing theoretical literature with the twofold aim of highlighting areas for future research and offering some guidance on how to use multidimensional methods in empirical and policy-oriented applications.
Keywords: D3; D63; I30; I32; 330; inequality; poverty; deprivation; multidimensional well-being; capabilities; functionings